Evaluation of multiplex flow cytometric opsonophagocytic assays for determination of functional anticapsular antibodies to Streptococcus pneumoniae. - Martinez, J; Clutterbuck, E; Li, H; Romero-Steiner, S; Carlone, G (2006)
The determination of functional antipneumococcal capsular polysaccharide antibodies by sequential testing of pre- and postvaccination serum samples one serotype at a time is sample-intensive and time-consuming and has a relatively low throughput. We tested several opsonophagocytic assay (OPA) formats, including the reference killing method, a monovalent bacterium-based flow method, a trivalent bacterium-based flow method, and a tetravalent bead-based flow method using a panel of sera (4 prevaccination and 16 postvaccination, from healthy adults immunized with the 23-valent pneumococcal polysaccharide vaccine). The trivalent and tetravalent methods allow simultaneous measurements of opsonic antibodies to multiple pneumococcal serotypes. The trivalent bacterial-flow OPA had significant correlation to the reference OPA method and to a previously published flow cytometric OPA (r values ranged from 0.61 to 0.91, P < 0.05) for serotypes 4, 6B, 9V, 14, 18C, 19F, and 23F. The tetravalent OPA had significant correlation to all OPA method formats tested (r values from 0.68 to 0.92, P < 0.05) for all seven serotypes tested. This tetravalent OPA is an alternative to other OPA methods for use during vaccine evaluation and clinical trials. Further, the flow cytometric multiplex OPA format has the potential for expansion beyond the current four serotypes to eight or more serotypes, which would further increase relative sample throughput while reducing reagent and sample volumes used.